Effect of Optimized Immunosuppression (Including Rituximab) on Anti-Donor Alloresponses in Patients With Chronically Rejecting Renal Allografts - Shiu, Kin Yee; Stringer, Dominic; McLaughlin, Laura; Shaw, Olivia; Brookes, Paul; Burton, Hannah; Wilkinson, Hannah; Douthwaite, Harriet; Tsui, Tjir-Li; Mclean, Adam; Hilton, Rachel; Griffin, Sian; et al. (Frontiers in Immunology, 2020)
RituxiCAN-C4 combined an open-labelled randomised controlled trial (RCT) in 7 UK centres to assess whether rituximab could stabilise kidney function in patients with chronic rejection, with an exploratory analysis of how B cell-depletion influenced T cell anti-donor responses relative to outcome. Between January 2007 and March 2015, 59 recruits were enrolled after screening, 23 of whom consented to the embedded RCT. Recruitment was halted when in a pre-specified per protocol interim analysis, the RCT was discovered to be significantly underpowered. This report therefore focuses on the exploratory analysis, in which we confirmed that when B cells promoted CD4+ anti-donor IFNγ production assessed by ELISPOT, this associated with inferior clinical outcome; these patterns were inhibited by optimised immunosuppression but not rituximab. B cell suppression of IFNγ production, which associated with number of transitional B cells and correlated with slower declines in kidney function was abolished by rituximab, which depleted transitional B cells for prolonged periods. We conclude that in this patient population, optimised immunosuppression but not rituximab promotes anti-donor alloresponses associated with favourable outcomes. Registered with EudraCT (2006-002330-38) and ClinicalTrials.gov (NCT00476164)